The health care mess : how we got into it and what it will take to get out - Richmond, Julius B. (Julius Benjamin), 1916-2008; Fein, Rashi (Cambridge, Mass. : Harvard University Press, 2005)
In this important new book, Julius Richmond and Rashi Fein recount the fraught history of health care in America since the 1960s, showing how the promises of medical advances have not been matched either by financing or by delivery of care. As a new crisis looms, and the existing patchwork of insurance is poised to unravel, American leaders must again take up the question of health care. This book brings the voice of reason and the promise of compromise to that debate.
The educational and scientific revolution : higher standards and changing practices -- The consumer revolution : increasing access to medical care -- Emerging tensions between regulation and market forces : dealing with growth -- Education for the health professions : the impact of growth -- The entrepreneurial revolution : a changing face for medicine -- Beyond the dollars : progress in health and the role of public health -- Medical challenges and opportunities -- Increasing equity : achieving universal health insurance.
Includes bibliographical references (pages 265-294) and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Medical care -- United States; Medical policy -- United States; Health planning -- United States; Medical care; Medical policy; Delivery of Health Care; Health Policy; United States; Patient Care; Soins médicaux -- États-Unis.; Politique sanitaire -- États-Unis.; Santé publique -- Planification -- États-Unis.; Prestation de soins; Politique sanitaire; Soins médicaux.; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Health planning; Medical care; Medical policy; United States; Gezondheidszorg; Verenigde Staten